Bureaucratic Structure in Implementing the “Anggrek” Waste Bank Program in Larangan Village, Candi District, Sidoarjo Regency - Desy Widiyanti; Ilmi Usrotin Choiriyah (Universitas Muhammadiyah Sidoarjo, 2021)
The environment is all forms that are around humans and can be an influence either directly or indirectly on human life. In order to realize waste management in accordance with applicable regulations, a waste bank program was created. One of the waste bank programs in Sidoarjo Regency is a waste bank in Larangan Village. One of the active waste banks in Larangan village is the “Anggrek” Garbage Bank which has received several award achievements. However, in its implementation the